Tinjauan Yuridis Pemberian Ganti Rugi Dalam Pengadaan Tanah Untuk Kepentingan Umum - D, Daud (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Land is a necessity for many people, it needs to be arranged in its use, this is regulated in the Basic Agrarian Law No. 5 of 1960, which covers, earth, water, and space with customary law as the main basis then how is the legal protection for land rights holders whose land area is affected by development for the public interest and the compensation process in land acquisition for the public interest. This study aims to (1) To find out and analyze the legal protection for land rights holders whose land is affected by development for the public interest (2) To find out and analyze the compensation process in land acquisition for the public interest. The type of research used in this study is empirical legal research while the data collection technique is the Statute Approach, Sociological Approach, Types of legal materials used, including primary legal materials and secondary legal materials. Data analysis is Analytical Descriptive Analysis. The results of the study show that (1) General description of the area including the location of the area, natural conditions and areas consisting of: Topography, Hydrology, Area of Land Use, Climate Conditions. ( 2 ) Legal Protection for Land Rights Holders Whose Land Area is Impacted by Development for Public Interest (3 ) The compensation process in land acquisition for public interest includes: Inventory and Identification, Compensation assessment, Deliberation on compensation determination, Provision of compensation, Form and amount of compensation.